Answer:
see explanation
Explanation:
The area (A) is calculated as
A = 3(2x + 1) = 6x + 3
Now 12 ≤ A ≤ 36 , that is
12 ≤ 6x + 3 ( subtract 3 from both sides )
9 ≤ 6x ( divide both sides by 6 )
1.5 ≤ x
and
6x + 3 ≤ 36 ( subtract 3 from both sides )
6x ≤ 33 ( divide both sides by 6 )
x ≤ 5.5
Put the 2 results together, then
1.5 ≤ x ≤ 5.5
Substitute the end values into length = 2x + 1
x = 1.5 : length = 2(1.5) + 1 = 3 + 1 = 4
x = 5.5 : length = 2(5.5) + 1 = 11 + 1 = 12
length can be between 4 and 12